Utilization of Humanism Value in Folklore in Ngawi Regency at Old Literature in University - Vinsca Sabrina Claudia; Sarwiji Suwandi; Nugraheni Eko Wardani (International Islamic Schools Alliance, 2021)
Learning old literature in University provides an introduction to students about past events and traditions that can ben applied to the living confitions of today’s society. In addition, it can provide a lesson about caring for humans and the environment. This makes the folklore of the origins of the village in Ngawi as an expression of oral literature that is packaged in to literary writings of local wisdom with humanism nuances. So, the point of attention in this research is the humanism value contained in folklore. The main problem in this research is about how to use humanism values in the development of old literary teaching materials in University. This study aims to describe and explain various humanism values as the use of old literature learning. The type of approach used is the humanism approach that focuses on the literary field. This study used a qualitative descriptive method by taking data in the form of content analysis. The results showed thet the folklore in Ngawi contained various kinds of humanism values contained in it, namely (1) Right Behavior; (2) Peace; (3) Truth; (4) Love, and (5) Nonviolence. On the other hand, folklore in Ngawi regency can provide an alternative as an old literature learning material as well as directing atudents to get to know the local culture thet occure in the surrounding environment.